Nutritional content and acceptability of milkfish and purple sweet potato sambusa in an effort to prevent stunting - Lydia Fanny; Nur Armadiah; Rudy Hartono (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Background: Stunting remains a major public health issue caused by chronic malnutrition and recurrent infections. In South Sulawesi, Indonesia, the prevalence of stunting in 2024 was 23.3%. One contributing factor is chronic energy deficiency (CED) among pregnant women. The government promotes supplementary feeding (PMT) to address this. Sambusa made from milkfish (Chanos chanos) and purple sweet potato has potential as a local PMT due to its nutritional value and local availability. Methods: This experimental study used a randomized design to analyze the sensory characteristics and nutritional content of Sambusa with milkfish and purple sweet potato substitution. The organoleptic test was conducted at the Organoleptic Laboratory of Poltekkes Kemenkes Makassar, and nutrient analysis (protein, omega-3, anthocyanin) at the Integrated Biotechnology Laboratory, Hasanuddin University, during May–June 2025. Results: Sensory evaluation showed significant differences in color and texture (p<0.05) but not in aroma or taste (p>0.05). The protein content in the control (F0) and best formula (F3) was 13.88% and 13.72%, respectively. The proportion of omega-3 to total fatty acids increased from 0.74% (F0) to 0.78% (F3), and anthocyanin levels rose from 2.57 CyE/g (F0) to 7.85 CyE/g (F3). Conclusion: Substitution with milkfish and purple sweet potato influenced the sensory and nutritional qualities of Sambusa. The modification enhanced omega-3 and anthocyanin content without significantly affecting protein levels. This product shows promise as a nutritious local supplementary food for pregnant women to help prevent stunting.